PERANCANGAN MUSEUM KOTA PONTIANAK - Humaira Humaira; Uray Fery Andi; Tri Wibowo Caesariadi (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2023)
A museum with artistic value and function is a building created to maintain and retell a silent evidence relating to the history of a field, place and nation. This design is intended as an effort to meet the needs of the Pontianak City museum which is also the discourse of the city government in the near future. The design of the Pontianak City Museum was deemed necessary, because as the provincial capital, Pontianak City is a city that has a variety of cultures. Heritage objects that need to be maintained and preserved need a place such as the city museum. The steps taken in designing the Pontianak City Museum were using the 5-step analysis design method by J.C Jones: Idea, Analysis, Synthesis, Evaluation, and Optimization. Data collection techniques in the design of the Pontianak City Museum used primary data obtained from observations and field interviews regarding visiting data and arrangements at the West Kalimantan Provincial Museum as well as secondary additional data collected from books and articles. The result of this design is the building design of the Pontianak City Museum which is included in the landscape of the riverside area with the adaptation of the iconic city monument. Consists of permanent and non-permanent showrooms, auditorium, storage and conservation rooms.